2018
DOI: 10.1016/j.wem.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Climbing-Related Injury Among Adults in the United States: 5-Year Analysis of the National Emergency Department Sample

Abstract: Most persons with climbing-related injuries presenting to EDs do not require inpatient admission. Although death is rare among patients with climbing-related injuries, the costs of injuries in survivors remain high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 14 publications
2
52
2
Order By: Relevance
“…Forrester et al performed a retrospective analysis of emergency department (ED) visits in the US from 2010 to 2014 [10]. They reported a weighted estimate of 15,116 adult ED visits associated with climbing-related injury.…”
Section: Injury Severity and Injury Patternmentioning
confidence: 99%
See 4 more Smart Citations
“…Forrester et al performed a retrospective analysis of emergency department (ED) visits in the US from 2010 to 2014 [10]. They reported a weighted estimate of 15,116 adult ED visits associated with climbing-related injury.…”
Section: Injury Severity and Injury Patternmentioning
confidence: 99%
“…The number of rock climbers presenting to US Emergency Departments for rock climbing-related injuries ranges from 3023 (±149) [10] to 3816 (±854) [12] per year. Schussmann et al found an incidence of 2.5 accidents per 1000 mountaineers per year or 5.6 injuries per 10,000 hours of mountaineering [13].…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations